Productive response of rabbits to supplemental copper in a diet based on tropical feedstuffs (1998)
Effects of supplemental copper in a diet based on tropical feedstuffs on productive performance, carcass measurements and haematology of rabbits were investigated in a 70d trial. Copper as CuS04.5H2O was supplemented at 0, 125, 250 and 375 mg kg-1 into a basal diet. The basal diet served as control treatment. Eight rabbits, each constituting a replicate, were fed on one of the experimental diets. The results showed that daily weight gain and feed intake of the rabbits fed 250 and 375 mg kg-1 supplemental copper were the highest followed by rabbits fed 125 mg kg-1 and the basal diet. Relative weights of the selected organs were similar except for the brain that tended to be lower in rabbits fed 250 and 375 mg kg-1 copper. Haemoglobin, packed cell volume and red blood counts were lower on 375 mg kg-1, however, haematological indices in rabbits fed 125 and 250 mg kg-1 were superior to other treatments. The results indicated that supplemental copper in a diet based on tropical feedstuffs improved performance, supported adequate organ development and might adversely affect haematopoiesis in rabbits at 375 mg kg-1 rate of inclusion.